Immunogenicity of the inactivated influenza vaccine in children who have undergone autologous stem cell transplant - Ryan, A.L.; Wadia, U.D.; Jacoby, P.; Cheung, Laurence; Kerr, F.; Fraser, C.; Tapp, H.; Carolan, L.A.; Laurie, K.L.; Barr, I.G.; Blyth, C.C.; Gottardo, N.G.; et al. (2019)
CORRESPONDENCE